Upaya Yang Dilakukan Guru PAI Dalam Menanamkan Nilai Kesopanan Peserta Didik di MI Ma’arif Soka Poncowarno - Umdatus Sukriyah; Siti Fatimah (IAINU Kebumen, 2023)
Politeness is the basis for the formation of the character of students who have the character of akhlakul karimah. By implementing a good personality, 50% of character education for students has been successful. This study aims to find out the steps taken by PAI teachers in instilling values that shape students to have polite personal character and good morals. The research location is MI Ma'arif Soka, Poncowarno District, Kebumen Regency. The theory used is the theory of instilling a character that reflects polite personality. Data collection techniques in the form of observation, interviews and document studies. The results of the research are that PAI teachers are coaching students, making notes of coaching that has been done, discussing with the head of the madrasa and other teachers in making decisions, working with parents or guardians of students, doing good habits to students and setting an example or a good role model for students. In improving polite personality for students, it must continue to be carried out with a focus on the problems of the students themselves.